PENGARUH PENGUASAAN KOSAKATA TERHADAP KEMAMPUAN DEBAT SISWA KELAS X SMA NEGERI 2 KUTACANE - Nila Nailupar; Ati Rosmiati; Lusi Selvia Fitri (Tuwah Pande: Jurnal Ilmu Pendidikan dan Pengajaran, 2022)
This study aims to determine the effect of vocabulary mastery on the debating ability of students in class X SMA Negeri 2 Kutacane. This type of research is a causal relationship correlation research. Data were collected using tests for class work answering vocabulary questions and conducting debates. The sample in this study was 52 students. The results of the research on vocabulary mastery of class X SMA Negeri 2 Kutacane were seen from 3 levels of assessment, namely high, medium, and low categories. Students who have a high level of vocabulary mastery in the high category are 5 students (15.4%), while students who have a moderate level of vocabulary mastery are 15 students (28.8%) and 29 students have a low category (55.8 %). Thus, it can be concluded that the students' vocabulary mastery is in the medium category. The interpretation of the least square formula values ​​a and b to determine the extent of the estimated influence between vocabulary mastery and debate with a simple linear regression formula Y=0.01+0.0012X is the regression coefficient of the vocabulary mastery variable (X) has a positive sign, which contains the implication that vocabulary mastery (X) affects students' debating ability (Y). The results of the F test, it is known that the Fcount of vocabulary mastery is 0.0067 while the Ftable is 7.16. Fcount is smaller than Ftable, then Ho is accepted and Ha is rejected, meaning = not significant. The conclusion means that this study proves the hypothesis which states that there is a significant and insignificant effect of vocabulary mastery on the debating ability of the tenth graders of SMA Negeri 2 Kutacane. The correlation between X and Y is categorized as having a weak relationship based on the results of the simple linear regression formula test and based on the significance test the results show tcount < t table or 0.0067 < 1.67 which means it is not significant.